Some Factors Influencıng Contınuance Intentıons To Use Electronıc Money Consumers In Indonesia - Annisa Puspitasari; Nur Khusniyah Indrawati; Raditha Hapsari (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
This study aims at examining the continued intention to use at electronics money consumer. Continued intention to use at electronics money consumer measured by security, trust, and customer satisfaction. This study obtained 162 respondents one of the largest citye in Indonesia, namely the greater city of Malang (including City of Malang, Malang Regency, and City of Batu). This study used SEM PLS and measured by SmartPLS 3.3.3. The result from this study are security and trust have a significant influence on the continued intention to use through consumer satisfaction as a mediation. The implication are the importance of increasing the sense of security, trust, and satisfaction of consumers so that they want to reuse electronic money; most consumers within the productive age who are very concerned about the security of electronic money and trusted electronic money institutions; most consumers are women; and it is also important to increase promotion, innovation, use of electronic money, to consumer loyalty of electronic money.